2004
DOI: 10.1007/s00531-003-0370-7
|View full text |Cite
|
Sign up to set email alerts
|

Coalification history of the Stephanian Ciñera-Matallana pull-apart basin, NW Spain: Combining anisotropy of vitrinite reflectance and thermal modelling

Abstract: The Stephanian Ciaeera-Matallana Basin of NW Spain comprises 1,500 m of alluvial to lacustrine coalbearing sediments, which were deposited in a late Variscan transtensional/transpressional pull-apart setting. The relationship between coalification pattern and rock deformation was evaluated by measurements of the anisotropy of vitrinite reflectance (AVR). The AVR ellipsoids reveal both pre-tectonic elements related to the bedding fabric and syn-tectonic elements related to folding, producing biaxial ellipsoid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…3.96 % Rmax) in rare cases, mostly in close association with sills (Botor et al 2009). Estimated geothermal gradients of 52 °C/km (Botor 2012) are lower than those at other Stephanian basins (Mendez 1985;Frings et al 2004;Ayllon et al 2003) and in the Palaeozoic basement (c. 35 °C/km; Brime et al 2001). Aller et al (2005) argued that increased heat flow due to hydrothermal-fluid circulation was the last important thermal episode in the SCZ, facilitated by pathways along faults.…”
Section: Geological Settingmentioning
confidence: 81%
See 4 more Smart Citations
“…3.96 % Rmax) in rare cases, mostly in close association with sills (Botor et al 2009). Estimated geothermal gradients of 52 °C/km (Botor 2012) are lower than those at other Stephanian basins (Mendez 1985;Frings et al 2004;Ayllon et al 2003) and in the Palaeozoic basement (c. 35 °C/km; Brime et al 2001). Aller et al (2005) argued that increased heat flow due to hydrothermal-fluid circulation was the last important thermal episode in the SCZ, facilitated by pathways along faults.…”
Section: Geological Settingmentioning
confidence: 81%
“…Therefore, new models (Fig. 3) were constructed taking into account previous thermal history studies in the SCZ (García-López et al 1997, 2007Ayllon 2003;Ayllon et al 2003;Frings et al 2004;Aller et al 2005;Frings and Warr 2012;Botor 2012), which indicated that the Late Carboniferous-Permian period was the main heating time. Vitrinite reflectance data were used to calculate the maximum palaeotemperatures (values T max 2 and T max 3 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations